2020
DOI: 10.1038/s41598-020-60753-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomics of active tuberculosis patients and contacts reveals unique processes activated during Mycobacterium tuberculosis infection

Abstract: Tuberculosis (TB) is the most lethal infection among infectious diseases. The specific aim of this study was to establish panels of serum protein biomarkers representative of active tB patients and their household contacts who were either infected (LtBi) or uninfected (eMi-tB Discovery cohort, Pontevedra Region, Spain). A TMT (Tamdem mass tags) 10plex-based quantitative proteomics study was performed in quintuplicate containing a total of 15 individual serum samples per group. Peptides were analyzed in an Lc-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Though the excellence of IGRA ELISA to differentiate NTM and TB infection in non-endemic countries was reported [ 70 ], 34–49% IGRA ELISA positive cases were reported in NTM in endemic countries [ 71 ]; this supports our hypothesis that the similarity of protein changes observed for both LTBI and NTM cases are explained by frequent coexistence of LTBI and NTM infection in our study community. The proteins of NTM that were identified in this study and previously described by Jusus et al [ 72 ] appear to reflect cross-reactivity observed between MTBC and NTM exposition. Two proteins such as the charged multivesicular body protein 4a (CHMP4A) and the platelet factor (PF)-4, were up-regulated in NTM as compared to HC and down-regulated in NTM as compared to active TB in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Though the excellence of IGRA ELISA to differentiate NTM and TB infection in non-endemic countries was reported [ 70 ], 34–49% IGRA ELISA positive cases were reported in NTM in endemic countries [ 71 ]; this supports our hypothesis that the similarity of protein changes observed for both LTBI and NTM cases are explained by frequent coexistence of LTBI and NTM infection in our study community. The proteins of NTM that were identified in this study and previously described by Jusus et al [ 72 ] appear to reflect cross-reactivity observed between MTBC and NTM exposition. Two proteins such as the charged multivesicular body protein 4a (CHMP4A) and the platelet factor (PF)-4, were up-regulated in NTM as compared to HC and down-regulated in NTM as compared to active TB in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Serum APOAI levels were negatively correlated with the onset of cerebral infarction in patients with carotid artery stenosis ( 43 ). Of note, a recent study demonstrated that APOAI, -AⅡ and -AⅣ were decreased in patients with active TB ( 44 ). Furthermore, rifampicin treatment led to an increase in the level of APOAI in patients with TB; however, there was no statistical significance ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sputum proteomics identified a five-protein signature differentiating between tuberculosis and nontuberculosis patients (sensitivity 70%, specificity 79%) [84]. Differential regulation of pro-inflammatory, lipid and iron transport proteins were revealed between patients with active tuberculosis and LTBI patients [74]. A serum three-protein signature distinguished MDR from drug-susceptible tuberculosis (sensitivity 81.2%, specificity 90%) and healthy controls (sensitivity 94.7%, specificity 80%) [85].…”
Section: Human Proteomic Signatures For Tuberculosis and Antituberculosis Treatment Responsesmentioning
confidence: 99%